The Effectiveness of Group Guidance Using Digital Journaling Techniques to Manage Overthinking in Children at the Sanggar Bimbingan Kampung Bharu, Malaysia - Ritonga, Muqri Izzan; Sri Ngayomi Yudha Wastuti (INDONESIAN COUNSELING AND PSYCHOLOGY, 2026)
The phenomenon of overthinking in school-aged children is increasing in the digital era, characterized by a tendency for children to experience excessive worry, difficulty managing emotions, and low self-reflection skills. This condition needs to be addressed through innovative Guidance and Counseling services that are appropriate for children's digital world. This study aims to analyze the effectiveness of group guidance using digital journaling techniques in managing overthinking in children under the guidance of the Kampung bharu Guidance Center, Malaysia. The study used a qualitative approach with a Guidance and Counseling Action Research (PTBK) design implemented in three cycles, involving 11 children aged 11–12 years. Each cycle includes planning, implementation, observation, and reflection stages, with digital journaling as an expressive medium to explore thoughts and emotions. Data were collected through participant observation, in-depth interviews, and content analysis of digital journaling, and analyzed using thematic analysis techniques. The results showed a significant increase in emotional well-being and self-regulation skills, with positive emotions increasing from 76.9% to 92.3%, negative emotions decreasing from 23.1% to 7.7%, and positive coping strategies increasing from 38.5% to 76.9%. This study confirms that digital journaling is effective in helping children recognize, manage, and reflect on overthinking. These findings offer an innovative intervention model that can be easily implemented in non-formal education to strengthen children's emotional regulation and mental resilience.